Unusual symptoms reveal a rare splenic lymphoma: a case report of PS-DLBCL with neck and shoulder pain as the initial presentation - Hu, Shifu; Hao, Yuanyuan; Liu, Xiangyu; Liu, Hanbo (Frontiers in Oncology, 2025)
The rare occurrence of diffuse large B-cell lymphoma (DLBCL) limited to the spleen presents difficulties in diagnosis. A case report details a patient whose initial symptoms were neck and shoulder pain, subsequently diagnosed as spontaneous spleen rupture, a rare complication of primary splenic lymphoma. Following a splenectomy, the patient was confirmed to have primary splenic DLBCL and made a good postoperative recovery. This report highlights the diagnostic dilemmas in atypical presentations, where neck and shoulder pain may be the only early sign of a neglected spleen rupture, lacking typical symptoms of the underlying disease. In cases of patients who are not stable, the recommended first imaging method is a focused assessment using sonography for trauma (FAST), as CT scans have a high level of sensitivity. Treatment is determined by hemodynamic status, with conservative management for stable patients and surgical intervention for unstable patients. The importance of recognizing spontaneous spleen rupture as a critical yet uncommon possibility in acute abdominal cases, especially in instances of primary splenic DLBCL, is emphasized in the report.